Correlation of sdLDL-C and Apob with the degree of cerebral artery stenosis in posterior circulation stroke - Zhaoyuan Sun; Jinzhi Liu; Aihua Wang; Zhihua Si (Scientific Reports)
Abstract Small and dense LDL cholesterol (sdLDL-C) and apolipoprotein B (ApoB) have important roles in promoting the development of atherosclerosis and are highly correlated with the degree of atherosclerosis. Several studies have found differences in anterior and posterior circulation strokes and in the mechanisms of their atherosclerosis, but little research has been done on the relationship of sdLDL-C and ApoB to atherosclerotic stenosis in anterior and posterior circulation strokes. We analyzed the correlation between sdLDL-C and ApoB and the degree of arterial stenosis in patients with posterior circulation stroke. We included 230 anterior circulation stroke (ACS) patients and 170 posterior circulation stroke (PCS) patients. Blood specimens were collected at admission, serum ApoB and sdLDL-C concentrations were measured, and the degree of arterial stenosis was determined on the basis of vascular imaging. We analyzed the predictive value of ApoB and sdLDL-C for the degree of cerebral artery stenosis in patients with PCS. For patients with nonmild stenosis, sdLDL-C and ApoB levels were higher in the PCS group than in the ACS group (P < 0.05). SdLDL-C (P < 0.001) and ApoB (P < 0.05) were independent risk factors for increased intracranial artery stenosis in the posterior circulation group. Binary logistic regression analysis showed that sdLDL-C (P < 0.05) and ApoB (P < 0.05) were independent risk factors for non-mild stenosis of the intracranial arteries in patients with PCS after correction for confounders. In the posterior circulation group, there was an interaction between the effects of sdLDL and ApoB on intracranial artery stenosis, P < 0.05. Plotting the ROC curve showed that the AUC of the combined detection of sdLDL-C and ApoB was 0.791, which was better than that of the single index. We built nomogram model, the DCA curves, calibration curves, NRI index, and IDI index of both the modeling and validation groups indicated that the diagnostic efficacy and clinical benefit of the combined sdLDL-C and ApoB assay were greater than those of single-indicator assays for cerebral artery stenosis in posterior circulation stroke. Risk factors contributing to the increased degree of intracranial arterial stenosis in ACS and PCS vary somewhat. SdLDL-C and ApoB may be of value in clinical decision making as predictors of cerebral arterial stenosis in patients with PCS.